Design and forming method for strengthening and toughening titanium-aluminum alloy laminated structure prepared through SLM
The Ti47Al2Cr2Nb/Ti6Al4V micro-laminated structure was prepared by SLM and in-situ gradient heat treatment was performed, which solved the problems of room temperature brittleness and poor toughness of the Ti47Al2Cr2Nb alloy, and achieved stable forming and toughening effects of micron-scale layer thickness.
Patent Information
- Application Number
- CN202511013735.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-08-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively solve the problem of grain boundary brittleness caused by room temperature brittleness and microstructure distribution of Ti47Al2Cr2Nb alloy. Especially in the preparation of complex titanium-aluminum alloy components, traditional alloying methods and additive manufacturing methods have difficulties. The interlayer bonding strength and toughness of the stacked structure are poor, making it difficult to achieve efficient forming of micro-laminated materials.
The Ti47Al2Cr2Nb/Ti6Al4V micro-laminated structure was prepared by SLM method. By forming a protruding structure on the Ti6Al4V tough layer and combining in-situ gradient heat treatment, the interlayer interconnection structure was designed to increase the crack propagation resistance between layers and achieve stacking strength and toughening.
The interlayer bonding capability and fracture toughness of the Ti47Al2Cr2Nb stacked structure are improved, and the stable forming of micron-scale layer thickness is achieved, which avoids the performance reduction caused by high-temperature preheating, and improves the overall strength and shapeability of the material.
Smart Images

Figure CN120516009A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing of metal composite structures, and specifically to a design and forming method for SLM-prepared structurally strengthened titanium aluminum alloy (Ti47Al2Cr2Nb) laminated structure, and more particularly to an in-situ strengthening and toughening design and additive manufacturing method for Ti47Al2Cr2Nb through structural design. Background Art
[0002] Ti47Al2Cr2Nb alloy has excellent high-temperature performance and corrosion resistance, which gives it obvious application advantages in the field of weapon protection. However, due to the intrinsic brittleness determined by the Ti-Al bonding method, the grain boundary brittleness caused by the microstructure distribution, and the environmental brittleness caused by oxygen and moisture, it has a great tendency to crack at room temperature and is difficult to process. There is still a long way to go before it can be applied in engineering, especially for the preparation of complex-shaped titanium-aluminum alloy components.
[0003] Room temperature brittleness is the biggest problem restricting the engineering application of Ti47Al2Cr2Nb alloy. Traditional alloying methods, such as adding Nb, Cr and other elements, have limited improvement in material properties. In recent years, many scholars have tried to use additive manufacturing to form Ti47Al2Cr2Nb alloy, but they still face many difficulties. Figure 6 The figure shows interlaced cracks generated in a 3D-printed Ti47Al2Cr2Nb specimen, and these cracks cannot be eliminated simply by adjusting parameters. Although electron beam powder bed technology can achieve 3D printing of titanium-aluminum alloys, it generally requires preheating to 600°C to 1200°C, which is extremely expensive. Excessively high preheating temperatures can cause extensive ablation of alloying elements. Kan et al. increased the Nb content in Ti47Al2Cr2Nb alloy, but electron beam additive manufacturing still required a preheating temperature as high as 1200°C. Therefore, there is an urgent need to develop structural and forming methods that improve the inherent brittleness of Ti47Al2Cr2Nb alloy and strengthen it. As early as 1999, Weiner et al. demonstrated that among various composite materials, a composite structure with an interlaced distribution of brittle and ductile phases, similar to bone-inspired structures, can form an effective energy dissipation structure, balance the internal stress distribution within the overall structure, and potentially overcome the performance limitations of single structural materials, simultaneously enhancing the strength and toughness of the structural system.
[0004] The forming method of laminated structures also faces great challenges. Studies have shown that the performance of laminated materials with multi-interface effects and small interlayer spacing is better than that of single materials. However, the current forming processes of laminated materials include spraying, vapor deposition, casting (pressure infiltration, etc.), etc. The mechanical properties of the prepared laminated materials are poor, and the thickness of the formed laminated materials is generally at the millimeter level. It is very difficult to control the thickness of micro-laminated materials (thickness below 0.1mm), and the interlayer bonding strength and toughness of heterogeneous laminated structures are very poor. New structural design and new process control strategies are urgently needed to improve the formability and comprehensive performance of Ti47Al2Cr2Nb alloy. Summary of the Invention
[0005] The present invention addresses the aforementioned shortcomings of the prior art by providing a method for designing and forming a structurally strengthened and toughened titanium aluminum alloy (Ti47Al2Cr2Nb) laminate structure fabricated using SLM. The present invention utilizes SLM to fabricate a Ti47Al2Cr2Nb / Ti6Al4V micro-laminated structure with interlayer strengthening and toughening. During the SLM process for fabricating the Ti47Al2Cr2Nb / Ti6Al4V micro-laminated structure, the composite structure undergoes an in-situ gradient heat treatment. This method employs a design for interconnected micro-laminated layers to increase the crack propagation resistance between the Ti47Al2Cr2Nb / Ti6Al4V layers, achieving a strengthened and toughened Ti47Al2Cr2Nb laminate design.
[0006] The purpose of the present invention is achieved through the following technical solutions: The present invention provides a method for designing and forming a structurally strengthened and toughened titanium aluminum alloy (Ti47Al2Cr2Nb) laminated structure prepared by SLM, comprising the following steps: S1. Using the SLM method, a Ti6Al4V tough layer is first formed on the substrate, a Ti6Al4V protrusion structure is formed on the Ti6Al4V tough layer, and then a Ti47Al2Cr2Nb brittle layer is formed on the Ti6Al4V tough layer. The above lamination steps are repeated to obtain a laminated structure part; S2. During the lamination process, the laminated structural alloy is subjected to in-situ gradient heat treatment to obtain a Ti47Al2Cr2Nb composite structural component with a strengthened and toughened structure.
[0007] As an embodiment of the present invention, during the preparation of the laminated structure component in step S1, the substrate is preheated at a temperature of 200-300°C.
[0008] As an embodiment of the present invention, in step S1, the thickness of the tough layer is 30-3000 μm, preferably 30-600 μm, more preferably 90-210 μm; the thickness of the brittle layer is 30-3000 μm, preferably 30-600 μm, more preferably 150-300 μm.
[0009] As an embodiment of the present invention, in step S1, the preparation parameters of the Ti6Al4V toughness layer are: laser power of 250~350W, scanning speed of 900~1100mm / s, and scanning spacing of 0.15~0.25mm.
[0010] As an embodiment of the present invention, in step S1, the Ti6Al4V protrusion structure includes one or more of a hemispherical shape, a mushroom shape, and a dendritic shape. The height of the Ti6Al4V protrusion structure is not higher than the height of the Ti47Al2Cr2Nb layer, preferably 30%-100% of the height of the Ti47Al2Cr2Nb brittle layer, more preferably 50%-100%, which is an integer multiple of the minimum powder layer thickness. A plurality of protrusion structures protruding from the Ti6Al4V toughness layer to the Ti47Al2Cr2Nb brittle layer are arrayed at the interface. The diameter of the Ti6Al4V protrusion structure is 30%-100% of the height of the Ti47Al2Cr2Nb brittle layer. The spacing of the Ti6Al4V protrusion structure is recommended to be 1 to 2 times the diameter, which increases the interlayer bonding strength and increases the resistance to interlayer crack propagation.
[0011] As an embodiment of the present invention, in step S1, the preparation parameters of the Ti6Al4V protrusion structure are: laser power of 250~350w, scanning speed of 900~1100mm / s, and scanning spacing of 0.15~0.25mm.
[0012] As one embodiment of the present invention, in step S1, the Ti47Al2Cr2Nb brittle layer is prepared using the following parameters: laser power of 900-1000W, scanning speed of 700-900mm / s, and scanning pitch of 0.15-0.25mm. The formation of the next Ti47Al2Cr2Nb layer involves remelting the previous Ti6Al4V layer.
[0013] As one embodiment of the present invention, in step S1, the thickness of a single powder coating is 20-40 μm, preferably 25-35 μm, and more preferably 30 μm. The thickness of the Ti6Al4V tough layer is 1-100 layers, preferably 1-20 layers, of powder coating; the thickness of the Ti47Al2Cr2Nb brittle layer is 1-100 layers, preferably 1-20 layers, of powder coating.
[0014] As an embodiment of the present invention, in step S2, the specific operation of the in-situ gradient heat treatment includes: according to the stress accumulation during the printing process, every printing period, the substrate and the inner cavity of the SLM device are subjected to in-situ heat treatment, and then cooled to the preheating temperature of the substrate until the preparation of the part is completed.
[0015] Preferably, in the in-situ gradient heat treatment, the temperature of the in-situ heat treatment is controlled at 450-500°C.
[0016] Preferably, the in-situ gradient heat treatment is performed every 14-36 mm of printing (the thickness of a single powder coating is 20-40 μm, preferably 600-1200 layers, including the Ti6Al4V tough layer and the Ti47Al2Cr2Nb brittle layer). During the in-situ heat treatment, the holding time is calculated according to the corresponding formula based on the total printed layer thickness.
[0017] Preferably, the time of in-situ heat treatment is Tmin, and its numerical relationship with the total thickness of printing at the current stage and the average area of the formed width at the current stage is: T 2 = , where the specific heat capacity of the laminated structure is c d J / (g℃), the density of the laminated structure is ρ d g / mm 3 , the total thickness of the current printing stage is t d mm, the thermal conductivity of the laminated structure is k d W / (mm℃), the average forming area at the current stage is A mm 2 , where c d , ρ d 、k d According to the actual measurement of the proportion of laminated materials, C is a constant 1 / (7.4×10 4 ).
[0018] Preferably, the specific heat capacity c of the laminated structure is d J / (g℃), density of the laminated structure ρ d g / mm 3 , thermal conductivity k of the laminated structure d W / (mm℃) is calculated as follows: Specific heat capacity of Ti47Al2Cr2Nb material c 4722 0.34×10 3 J / (kg℃), density ρ 4722 3.8g / mm 3 , thermal conductivity k 4722 is 18.6W / (m℃)); Specific heat capacity of Ti6Al4V material c 64 0.54×10 3 J / (kg℃), density ρ 64 4.43g / mm 3 , thermal conductivity k 64 15.25W / (m℃)); The specific heat capacity of the composite structure of Ti47Al2Cr2Nb and Ti6Al4V with a thickness of D1mm is calculated as the specific heat capacity c of the laminated structure. d J / (g℃)=(c 4722 ×D1+c 64 ×D2) / ( D1+ D2) J / (kg℃), calculated according to the same rule, the density of the laminated structure ρ d g / mm 3 , thermal conductivity k of the laminated structure d W / (mm℃).
[0019] Preferably, during the in-situ heat treatment, the cooling rate is 3-5°C / min. Excessively high cooling rates can generate significant interlaminar stresses, leading to significant deformation of the part. Due to the differences in deformation capacity between dissimilar materials, interlaminar cracks can easily develop. Excessively low cooling rates can lead to significant grain growth, impairing part performance.
[0020] The present invention also provides a titanium aluminum alloy (Ti47Al2Cr2Nb) composite structural part prepared according to the above method, in which the interlayer bonding ability is stronger and the fracture toughness is improved by 30% to 62Mpa·m 1 / 2 .
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes the SLM method to prepare Ti47Al2Cr2Nb / Ti6Al4V micro-laminated structural parts. The interlaminar bonding strength and the resistance to interlaminar crack propagation are increased by designing microscopic toughness protrusions between the laminates in the additive manufacturing model. In addition, through in-situ heat treatment measures during the forming process, the interlaminar fracture toughness of the laminated material is improved by optimizing the combination of in-situ heat treatment frequency gradient control, heat treatment temperature, laminate thickness matching, and protrusion structure design, thereby realizing additive forming of difficult-to-form Ti47Al2Cr2Nb alloy thermal protection material blocks.
[0022] (2) Compared with the traditional Ti47Al2Cr2Nb / Ti6Al4V laminated structure roll forming technology, the present invention adopts SLM forming, which achieves micro-laminated control of micron-level layer thickness, improves the consistency and performance stability of the formed parts, and avoids repeated external heating treatment processes; (3) Compared with the traditional Ti47Al2Cr2Nb / Ti6Al4V laminated structure, the present invention adopts an interlayer micro-protrusion structure design to increase interlayer toughness, change the propagation direction of interlayer cracks, increase the resistance to interlayer crack initiation and propagation, and improve the toughness of laminated parts; (4) Compared with the traditional Ti47Al2Cr2Nb / Ti6Al4V laminated structure, the present invention reduces the residual stress of the laminated structure by in-situ gradient heat treatment, and formulates a non-uniform frequency in-situ heat treatment system according to the internal stress accumulation as the number of layers increases during the SLM forming process. The interlayer fracture toughness of the laminated structure after treatment is improved by 30%, and the gradient heat treatment avoids the increase in grain size caused by excessively high cumulative temperature, which leads to a decrease in the performance of the entire component.
[0023] (5) The method of the present invention is simple to operate, easy to control the process, does not require external equipment, and can simply and effectively improve the performance of the material and reduce the residual stress of the material, providing great potential for the application of additive manufacturing technology of medium-temperature protective materials represented by Ti47Al2Cr2Nb in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Other features, objects and advantages of the present invention will become more apparent upon reading the detailed description of non-limiting embodiments with reference to the following drawings: Figure 1 Schematic diagram of the internal features of the composite structure of the present invention; Figure 2 This is a macroscopic sample of the composite structure prepared in Example 1 of the present invention; Figure 3 The microstructure of the composite structure prepared in Example 1 of the present invention; Figure 4 This is a picture of the sample of Comparative Example 1 that experienced interlayer cracking during the forming process; Figure 5 This is a picture of the sample of Comparative Example 4 that experienced interlayer cracking during the forming process; Figure 6 The cracking phenomenon of Ti47Al2Cr2Nb alloy during additive manufacturing. a is the macroscopic morphology of the crack, and b is the microscopic composition of the crack area. Figure 7 This is the composite structure macro sample and micro structure prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0025] The present invention will be described in detail below with reference to specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those skilled in the art, several variations and improvements can be made without departing from the scope of the present invention. These all fall within the scope of protection of the present invention.
[0026] The present invention provides a SLM-prepared structural toughening Ti47Al2Cr2Nb laminated structure, such as Figure 1 The preparation method comprises the following steps: A. Design interconnected structures such as tough protrusions between micro-laminated layers to increase the crack propagation resistance between Ti47Al2Cr2Nb / Ti6Al4V layers and achieve a strong and tough design for Ti47Al2Cr2Nb laminates; B. Prepare Ti47Al2Cr2Nb / Ti6Al4V micro-laminated structure with interlayer strengthening and toughening structure by SLM method; C. During the SLM preparation of Ti47Al2Cr2Nb / Ti6Al4V micro-laminated structure parts, the composite structure is subjected to in-situ gradient heat treatment; the specific operations of the in-situ gradient heat treatment include: heating and keeping the substrate and inner cavity of the SLM equipment warm for each fixed height printed according to the stress accumulation during the printing process, the holding time is calculated according to the formula, and then cooling to the preheating temperature of the substrate until the part is prepared.
[0027] In the following embodiments, the in-situ heat treatment time is Tmin, and its numerical relationship with the total thickness of the printing at the current stage and the average area of the formed format at the current stage is (i.e., the printing time required for the in-situ heat treatment to be performed): T 2 = , where the specific heat capacity of the laminated structure is c d J / (g℃), the density of the laminated structure is ρ d g / mm 3 , the total thickness of the current printing stage is t d mm, the thermal conductivity of the laminated structure is k d W / (mm℃), the average forming area at the current stage is A mm 2 , the gradient in-situ heat treatment time is T min, where c d , ρ d 、k d According to the actual measurement of the proportion of laminated materials, C is a constant 1 / (7.4×10 4 The frequency of heat treatment is one in-situ heat treatment every 18 to 36 mm of printing.
[0028] Example 1 A method for designing and forming a structurally strengthened and toughened Ti47Al2Cr2Nb laminated structure prepared by SLM, comprising the following steps: (1) Using computer 3D modeling software to create a 100×100×90mm 3 3D model (the average forming area at this stage is 100×100mm 2 ), save as stl format; (2) Import the 3D model in step (1) into the additive manufacturing model processing software. The raw materials are Ti47Al2Cr2Nb (specific heat capacity c 47220.34×10 3 J / (kg℃), density ρ 4722 3.8g / mm 3 , thermal conductivity k 4722 18.6W / (m℃)) and Ti6Al4V (specific heat capacity c 64 0.54×10 3 J / (kg℃), density ρ 64 4.43g / mm 3 , thermal conductivity k 64 The thickness of the composite structure of 0.3mmTi47Al2Cr2Nb and 0.15mmTi6Al4V is selected for thickness matching, and its specific heat capacity is calculated as the specific heat capacity of the laminated structure c d J / (g℃)=(c 4722 ×0.3+c 64 ×0.15) / (0.3+0.15) is 0.41×10 3 J / (kg℃)= 0.41 J / (g℃), calculated according to the same rule, the density of the laminated structure ρ d g / mm 3 3.97g / mm 3 , the thermal conductivity k of the laminated structure d W / (mm℃) is 17.6W / (m℃)= 17.6×10 -3 W / (mm℃).
[0029] The Ti47Al2Cr2Nb layer was produced with a laser power of 1000W, a scanning speed of 800mm / s, a layer thickness of 300μm, and a scanning pitch of 0.20mm. The Ti6Al4V layer was produced with a laser power of 300W, a scanning speed of 1000mm / s, a layer thickness of 150μm, and a scanning pitch of 0.20mm. The single-pass powder coating thickness for both the brittle and ductile layers was 30μm, enabling both single-layer and multi-layer coating. Slicing, layering, and path filling commands were executed, and the resulting file was exported to a device-readable format. (3) Perform equipment inspection and parameter setting. The substrate preheating temperature is 200°C and the oxygen content is controlled below 800 ppm. Import the file generated in step (2) into the equipment for SLM manufacturing; (4) During the preparation process, the thickness matching is that the thickness of the Ti6Al4V single layer is 150μm, and the thickness of the Ti47Al2Cr2Nb single layer Dt is 300μm. First, the SLM method is used to form a 150μm Ti6Al4V, and the parameters are the Ti6Al4V parameters described in step (2). Then, according to the protrusion structure design, a protrusion with a thickness of Dt=300μm (hemispherical, with a spacing of 1.5Dt) is formed. After the forming is completed, the Ti6Al4V powder outside the protrusion structure is blown off (the forming parameters are the same as those of the Ti6Al4V layer), and the powder cylinder is replaced for Ti47Al2Cr2Nb powder SLM forming, with a powder thickness of Dt, and the forming parameters are the Ti47Al2Cr2Nb parameters described in step (2).
[0030] (5) During the preparation process, the formed parts are subjected to in-situ gradient heat treatment. According to the formula, if the printing thickness of each stage is 18 mm (600 layers), then 5 in-situ heat treatments are required to print 90 mm. The total thickness of the first stage printing is t d =18mm, heat treatment temperature is 450℃, heat treatment time is 15min, the total thickness of the second stage printing is t d =32mm, heat treatment temperature is 450℃, heat treatment time is 20min, total thickness of the third stage printing is t d =54mm, heat treatment temperature is 450℃, heat treatment time is 24min, the total thickness of the fourth stage printing is t d =72mm, heat treatment temperature is 450℃, heat treatment time is 28min, the total thickness of the fifth stage printing is t d =90mm, heat treatment temperature is 450℃, heat treatment time is 31.5min. The in-situ heat treatment process is to heat the substrate to 450℃ at 10℃ / min, keep it at this temperature for a certain time, and then cool it to the substrate preheating temperature at a rate of 5℃ / min. The macro specimen of the SLM formed laminated material formed by the in-situ gradient heat treatment is as follows Figure 2 As shown, the microstructure Figure 3 shown.
[0031] The calculation process is as follows. To facilitate engineering applications, the minimum time unit is accurate to half a minute and is rounded up approximately.
[0032] T1 2 = = , therefore, T1=15 (min); T2 in t d is 32 (mm), and the calculated time T2 = T1 =20 (min); T3 mid d is 54 (mm), and the calculated time T3=T2 24 (min); T4 in t d is 72 (mm), and the calculated time T4 = T3 28 (min); T4 in t d is 90 (mm), and the calculated time T5=T4 31.5 (min); In this embodiment, the interlaminar crack propagation in the Ti6Al4V and Ti47Al2Cr2Nb laminated structures prepared by direct SLM was improved from a straight path to a multi-branched path, and the interlaminar fracture toughness of the specimen was improved by more than 30% compared with the Ti6Al4V / Ti47Al2Cr2Nb laminated structure without protrusions.
[0033] Example 2 A method for designing and forming a structurally strengthened and toughened Ti47Al2Cr2Nb laminated structure prepared by SLM, comprising the following steps: (1) Using computer 3D modeling software to create a 220×150×90mm 3 3D model (the average forming area at the current stage is 220×150mm 2 ), save as stl format; (2) Import the 3D model in step (1) into the additive manufacturing model processing software. The raw materials are Ti47Al2Cr2Nb (specific heat capacity c 4722 0.34×10 3 J / (kg℃), density ρ 4722 3.8g / mm 3 , thermal conductivity is 18.6W / (m℃)) and Ti6Al4V (specific heat capacity c 64 0.54×10 3 J / (kg℃), density ρ 64 4.43g / mm 3 , thermal conductivity is 15.25W / (m℃)). Thickness matching is selected for the composite structure of 0.15mmTi6Al4V and 0.15mmTi47Al2Cr2Nb. The specific heat capacity is roughly calculated as the specific heat capacity of the laminated structure c d J / (g℃) is 0.44×10 3 J / (kg℃), density of the laminated structure ρ d g / mm 3 4.115g / mm 3 , the thermal conductivity k of the laminated structure d W / (mm℃) is 16.925W / (m℃).
[0034] The Ti47Al2Cr2Nb layer uses a laser power of 1000W, a scanning speed of 800mm / s, a layer thickness of 150μm, and a scanning pitch of 0.20mm. The Ti6Al4V layer uses a laser power of 300W, a scanning speed of 1000mm / s, a layer thickness of 150μm, and a scanning pitch of 0.20mm. The layer thickness of a single powder application is 30μm, and both single-layer and multi-layer powder application can be achieved. Slicing, layering, and path filling commands are executed, and the file is exported to a file format that the device can recognize. (3) Perform equipment inspection and parameter setting. The substrate preheating temperature is 200°C and the oxygen content is controlled below 800 ppm. Import the file generated in step (2) into the equipment for SLM manufacturing; (4) During the preparation process, the thickness matching is that the thickness of the Ti6Al4V single layer is 150μm, and the thickness Dt of the Ti47Al2Cr2Nb single layer is 150μm. First, the SLM method is used to form 0.15mm Ti6Al4V, and the parameters are the Ti6Al4V parameters described in step (2). Then, according to the protrusion structure design, a protrusion with a thickness of 60% Dt = 0.09mm (hemispherical, with a spacing of 1.5Dt) is formed. After the forming is completed, the Ti6Al4V powder outside the protrusion structure is blown off (the forming parameters are the same as those of the Ti6Al4V layer), and the powder cylinder is replaced for Ti47Al2Cr2Nb powder SLM forming, with a powder thickness of Dt, and the forming parameters are the Ti47Al2Cr2Nb parameters described in step (2).
[0035] (5) During the preparation process, the formed parts are subjected to in-situ gradient heat treatment. According to the formula, if the printing thickness of each stage is 30 mm (1000 layers), then 3 in-situ heat treatments are required to print 90 mm. The total thickness of the first stage printing is t d =30mm, heat treatment temperature is 450℃, heat treatment time is 37.9min, the total thickness of the second stage printing is t d =60mm, heat treatment temperature is 450℃, heat treatment time is 53.6min, total thickness of the third stage printing is t d =90mm, heat treatment temperature is 450℃, and heat treatment time is 63.6min. The in-situ heat treatment process is to heat the substrate to 450℃ at 10℃ / min, keep it at this temperature for a certain period of time, and then cool it to the substrate preheating temperature at a rate of 5℃ / min. The SLM formed laminated material after in-situ gradient heat treatment is formed into a laminated material.
[0036] The calculation process is as follows; T1 2 = = , therefore, T1=37.9 (min); T2 in t dis 36 (mm), and the calculated time T2 = T1 =53.6 (min); T3 mid d is 54 (mm), and the calculated time T3=T2 63.6 (min). In this example, the interlaminar crack propagation in the Ti6Al4V and Ti47Al2Cr2Nb stacked structures prepared by direct SLM was improved from a straight path to a multi-branched path, and the interlaminar fracture toughness of the sample reached 66.56 MPa·m 1 / 2 .
[0037] Example 3 A method for designing and forming a structurally strengthened and toughened Ti47Al2Cr2Nb laminated structure prepared by SLM, comprising the following steps: (1) Use computer 3D modeling software to create a 100×100×90mm 3 The three-dimensional model is saved in stl format; (2) Import the 3D model in step (1) into the additive manufacturing model processing software. The raw materials are Ti47Al2Cr2Nb (specific heat capacity c 4722 0.34×10 3 J / (kg℃), density ρ 4722 3.8g / mm 3 , thermal conductivity is 18.6W / (m℃)) and Ti6Al4V (specific heat capacity c 64 0.54×10 3 J / (kg℃), density ρ 64 4.43g / mm 3 , thermal conductivity is 15.25W / (m℃)). Thickness matching is selected for the composite structure of 0.3mmTi47Al2Cr2Nb and 0.15mmTi6Al4V. The specific heat capacity is roughly calculated as the specific heat capacity of the laminated structure c d J / (g℃) is 0.41×10 3 J / (kg℃), density of the laminated structure ρ d g / mm 3 3.97g / mm 3 , the thermal conductivity k of the laminated structure d W / (mm℃) is 17.6W / (m℃).
[0038] The Ti47Al2Cr2Nb layer was produced with a laser power of 1000W, a scanning speed of 800mm / s, a layer thickness of 300μm, and a scanning pitch of 0.20mm. The Ti6Al4V layer was produced with a laser power of 300W, a scanning speed of 1000mm / s, a layer thickness of 150μm, and a scanning pitch of 0.20mm. The layer thickness of a single powder application was 30μm, and both single-layer and multi-layer powder application were possible. Slicing, layering, and path filling commands were executed, and the file was exported to a device-readable file format. (3) Perform equipment inspection and parameter setting. The substrate preheating temperature is 200°C and the oxygen content is controlled below 800 ppm. Import the file generated in step (2) into the equipment for SLM manufacturing; (4) During the preparation process, the SLM method is first used to form a 0.15 mm thick Ti6Al4V layer, and the parameters are the same as those for the Ti6Al4V layer described in step (2). Then, a protrusion with a thickness of 50% Dt = 0.15 mm (hemispherical shape with a spacing of 1.5 Dt) is formed according to the protrusion structure design. After the protrusion structure is formed, the Ti6Al4V powder outside the protrusion structure is blown away (the forming parameters are the same as those for the Ti6Al4V layer), and the powder cylinder is replaced for SLM forming of Ti47Al2Cr2Nb powder. The powder thickness is Dt = 0.3 mm, and the forming parameters are the same as those for the Ti47Al2Cr2Nb layer described in step (2).
[0039] (5) During the preparation process, the formed parts are subjected to in-situ gradient heat treatment. According to the formula, if the printing thickness of each stage is 18mm (600 layers), 18mm, 36mm (1200 layers), and 18mm, then 4 in-situ heat treatments are required to print 90mm. The total printing thickness of the first stage is t d =18mm, heat treatment temperature is 450℃, heat treatment time is 15min, the total thickness of the second stage printing is t d =36mm, heat treatment temperature is 450℃, heat treatment time is 20min, total thickness of the third stage printing is t d =72mm, heat treatment temperature is 450℃, heat treatment time is 28min, the total thickness of the fourth stage printing is t d =90mm, heat treatment temperature is 450℃, and heat treatment time is 31.5min. The in-situ heat treatment process is to heat the substrate to 450℃ at 10℃ / min, hold the temperature for the corresponding time, and then cool it to the substrate preheating temperature at a rate of 5℃ / min. The SLM-molded laminated material undergoes in-situ gradient heat treatment.
[0040] The calculation process is consistent with that of Example 1.
[0041] Example 4 A method for designing and forming a structurally strengthened and toughened Ti47Al2Cr2Nb laminated structure prepared by SLM, comprising the following steps: (1) Using computer 3D modeling software to create a 220×150×90mm 3 The three-dimensional model is saved in stl format; (2) Import the 3D model in step (1) into the additive manufacturing model processing software. The raw materials are Ti47Al2Cr2Nb (specific heat capacity c 4722 0.34×10 3 J / (kg℃), density ρ 4722 3.8g / mm 3 , thermal conductivity k 4722 18.6W / (m℃)) and Ti6Al4V (specific heat capacity c 64 0.54×10 3 J / (kg℃), density ρ 64 4.43g / mm 3 , thermal conductivity k 64 The thickness of the composite structure is 0.15mmTi6Al4V and 0.15mmTi47Al2Cr2Nb, and the specific heat capacity is roughly calculated as c. d J / (g℃) is 0.44×10 3 J / (kg℃), density ρ d g / mm 3 4.115g / mm 3 , thermal conductivity k d W / (mm℃) is 16.925W / (m℃).
[0042] The Ti47Al2Cr2Nb layer uses a laser power of 900W, a scanning speed of 800mm / s, a powder layer thickness of 150μm, and a scanning pitch of 0.20mm. The Ti6Al4V layer uses a laser power of 300W, a scanning speed of 1000mm / s, and a scanning pitch of 0.20mm. The minimum layer thickness is 30μm, and both single-layer and multi-layer powder coating can be achieved. Slicing, layering, and path filling commands are executed, and the file is exported to a device-readable format. (3) Perform equipment inspection and parameter setting. The substrate preheating temperature is 300°C and the oxygen content is controlled below 800 ppm. Import the file generated in step (2) into the equipment for SLM manufacturing; (4) During the preparation process, the thickness matching is 150μm for the Ti6Al4V single layer and 150μm for the Ti47Al2Cr2Nb single layer. First, the SLM method is used to form a 0.15mm Ti6Al4V, and the parameters are the same as those for Ti6Al4V in step (2). Then, a protrusion with a thickness of 60% Dt = 0.09mm is formed according to the protrusion structure design. After forming, the Ti6Al4V powder outside the protrusion structure is blown away, and the powder cylinder is replaced for SLM forming of Ti47Al2Cr2Nb powder. The powder thickness is Dt, and the forming parameters are the same as those for Ti47Al2Cr2Nb in step (2).
[0043] (5) During the preparation process, the formed parts are subjected to in-situ gradient heat treatment. According to the formula, if the printing thickness of each stage is 30 mm (1000 layers), then 3 in-situ heat treatments are required to print 90 mm. The total thickness of the first stage printing is t d =30mm, heat treatment temperature is 500℃, heat treatment time is 37.9min, the total thickness of the second stage printing is t d =60mm, heat treatment temperature is 500℃, heat treatment time is 53.6min, total thickness of the third stage printing is t d =90mm, heat treatment temperature is 500℃, heat treatment time is 63.6min. The in-situ heat treatment process is to heat the substrate to 500℃ at 10℃ / min, keep it at this temperature for a certain time, and then cool it to the substrate preheating temperature at a rate of 3℃ / min. The microstructure of the SLM formed laminated material formed by in-situ gradient heat treatment is as follows Figure 7 The calculation process is consistent with that of Example 2.
[0044] In this embodiment, the interlaminar fracture toughness of the Ti6Al4V and Ti47Al2Cr2Nb laminated structure specimens prepared directly by SLM reached 67.06 MPa·m 1 / 2 .
[0045] Comparative Example 1 This comparative example provides a method for designing and forming a structurally toughened Ti47Al2Cr2Nb laminated structure prepared by SLM. The specific steps are basically the same as those in Example 1, except that: in this comparative example, In step (2), no TC4 toughness layer is provided, i.e., a single Ti47Al2Cr2Nb material is formed; In step (5), the printing thickness and heat treatment time of each stage are fixed, and the gradient heat treatment time of 15, 20, 24, 28, and 31.5 minutes is performed for each stage respectively according to the formula.
[0046] The Ti47Al2Cr2Nb structure SLM formed specimen thus obtained exhibited interlaminar cracking during the forming process. Figure 4 shown.
[0047] Comparative Example 2 This comparative example provides a method for designing and forming a structurally toughened Ti47Al2Cr2Nb laminated structure prepared by SLM. The specific steps are basically the same as those in Example 1, except that: In step (4), no tough dendritic structure is set; In step (5), the printing thickness and heat treatment time of each stage are fixed, and the gradient heat treatment time of 15, 20, 24, 28, and 31.5 minutes is performed for each stage respectively according to the formula.
[0048] The interlaminar fracture toughness of the SLM formed sample of Ti6Al4V and Ti47Al2Cr2Nb laminated structure thus prepared is 15MPa·m 1 / 2 about.
[0049] Comparative Example 3 This comparative example provides a method for designing and forming a structurally toughened Ti47Al2Cr2Nb laminated structure prepared by SLM. The specific steps are basically the same as those in Example 1, except that: in this comparative example, In step (4), a tough Ti6Al4V array protrusion structure with a height of 0.15 mm is provided; In step (5), no segmented in-situ gradient heat treatment is performed. The sample is heat treated once. After printing 90 mm, the sample is heat treated at a temperature of 450 ° C and a holding time of 30 min.
[0050] The interlaminar fracture toughness of the SLM-formed specimen of the Ti6Al4V and Ti47Al2Cr2Nb laminated structure thus prepared is 10.30 MPa·m 1 / 2 .
[0051] Comparative Example 4 This comparative example provides a method for designing and forming a structurally toughened Ti47Al2Cr2Nb laminated structure prepared by SLM. The specific steps are basically the same as those in Example 1, except that: in this comparative example, In step (4), a tough Ti6Al4V array protrusion structure with a height of 0.15 mm is provided; In step (5), the printing thickness of each stage is fixed, and the heat treatment is performed in five stages of 15, 15, 15, 15, and 15 minutes for each stage respectively according to the formula.
[0052] The SLM formed specimens of Ti6Al4V and Ti47Al2Cr2Nb laminated structures thus obtained exhibited interlaminar cracking in the latter stages. Figure 5 shown.
[0053] The present invention has many specific application paths, and the above is only a preferred embodiment of the present invention. It should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. For those skilled in the art, several improvements can be made without departing from the principles of the present invention, and these improvements should also be considered as the scope of protection of the present invention.
Claims
1. A design and forming method for a structurally strengthened and toughened titanium-aluminum alloy laminated structure prepared by SLM, characterized in that: The steps include: S1. Using the SLM method, a tough layer is first formed on a substrate, a protrusion structure is formed on the tough layer, and then a brittle layer is formed on the tough layer. The steps of preparing the tough layer, the protrusion structure, and the brittle layer are repeated to obtain a laminated structure part. S2. During the preparation process, the laminated structural parts are subjected to in-situ gradient heat treatment to obtain structurally strengthened and toughened composite structural parts; In step S2, the specific operation of the in-situ gradient heat treatment includes: performing in-situ heat treatment on the substrate and the inner cavity of the SLM device every printing period according to the stress accumulation during the printing process, and then cooling to the preheating temperature of the substrate until the part is completed; The temperature of in-situ heat treatment is controlled at 450~500℃; The frequency of in-situ heat treatment is once every 14 to 36 mm of printing; The in-situ heat treatment time is Tmin, and its numerical relationship with the total thickness of the current printing stage and the average area of the current forming format is: T 2 = , where the specific heat capacity of the laminated structure is c d J / (g℃), the density of the laminated structure is ρ d g / mm 3 , the total thickness of the current printing stage is t d mm, the thermal conductivity of the laminated structure is k d W / (mm℃), the average forming area at the current stage is A mm 2 , where c d , ρ d 、k d According to the actual measurement of the proportion of laminated materials, C is a constant 1 / (7.4×10 4 ).
2. The design and forming method according to claim 1, characterized in that: In step S1, the material of the brittle layer is Ti47Al2Cr2Nb; and / or, the material of the toughness layer is Ti6Al4V; And / or, the material of the protrusion structure is Ti6Al4V.
3. The design and forming method according to claim 1, characterized in that: During the preparation of the laminated structure component in step S1, the substrate is preheated at a temperature of 200-300°C.
4. The design and forming method according to claim 1, characterized in that: In step S1, the preparation parameters of the toughness layer are: laser power of 250-350 W, scanning speed of 900-1100 mm / s, and scanning spacing of 0.15-0.25 mm; and / or, preparation parameters of the brittle layer: laser power of 900-1000 W, scanning speed of 700-900 mm / s, scanning spacing of 0.15-0.25 mm; and / or, the preparation parameters of the protrusion structure are: laser power of 250-350 W, scanning speed of 900-1100 mm / s, and scanning spacing of 0.15-0.25 mm; And / or, during the preparation of the tough layer, the brittle layer, and the protrusion structure, the thickness of a single powder spreading layer is 20-40 μm.
5. The design and forming method according to claim 1, characterized in that: In step S1, the protrusion structure includes one or more of a hemispherical shape, a mushroom shape, and a dendritic shape; And / or, the height of the protrusion structure is not higher than the height of the brittle layer.
6. The design and forming method according to claim 1, characterized in that: During the in-situ heat treatment, the cooling rate when cooling to the substrate is 3-5°C / min.
7. A titanium-aluminum alloy composite structural part prepared by the design and forming method according to claim 1.
Citation Information
Cited By
SLM preparation method of weak-anisotropy strengthened and toughened titanium-aluminum alloy micro-laminated structure and workpiece
CN122007438A